Immuno-monitoring reveals an extended subclinical disease activity in tocilizumab-treated giant cell arteritis. (28th June 2018) - Gloor, Andrea D; Yerly, Daniel; Adler, Sabine; Reichenbach, Stephan; Kuchen, Stefan; Seitz, Michael; Villiger, Peter M
Abstract: Objective: Tocilizumab is effective in inducing and maintaining remission of GCA. Despite clinical and serological control of disease, magnetic resonance angiography may show persistence of inflammatory signals of unknown significance in arterial walls. Thus, there is an unmet need for tools to detect subclinical disease activity. Methods: Immune–inflammatory markers were measured in prospectively collected sera of the first randomized, double-blind, placebo-controlled trial investigating the use of tocilizumab in GCA. As a comparison, immune–inflammatory markers were also measured in sera from age- and sex-matched healthy volunteers. The biomarkers were quantified using luminex technology. Results: Of all the parameters determined, only MMP-3, pentraxin-3 and sTNFR2 were significantly elevated, while ICAM-1 and CD163 were significantly decreased during the early stages of the study, at time points of full clinical remission under treatment with tocilizumab plus glucocorticoids. In contrast, tocilizumab monotherapy towards the end of the study resulted in an almost complete normalization of immune–inflammatory molecules, as defined by the healthy controls. MMP-3 levels showed a weak association with magnetic resonance signal intensity; none of the biomarkers predicted relapse occurring within 6 months after study end. Conclusion: The data documented a subclinical disease activity in GCA that was more pronounced during the early stages of treatment and almost disappeared towards the study end. They indicated that tocilizumab treatment of at least 52 weeks is necessary in order to reset a broad range of immune–inflammatory pathways. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT01450137.